Generation of general system parameters for Rainbow electronic signature scheme for 384 and 512 security bits - Yesina, M.V.; Kandiy, S.O.; Ostryanska, E.V.; Gorbenko, I.D. (Radiotekhnika, 2021)
Today, there is rapid progress in the creation of quantum computers to solve various computational problems and for different purposes. At the same time, special efforts are made to create such a quantum computer that can solve the problems of cryptanalysis of existing cryptosystems: asymmetric ciphers, key encapsulation protocols, electronic signatures, etc. Prevention of such threats can be achieved by developing cryptographic systems that will be protected against both quantum and classical attacks, and be able to interact with existing protocols and communication networks. There is also a significant need for protection against attacks by side channels. Currently, significant efforts of cryptologists are focused on the NIST PQC open competition. The main idea of the NIST PQC competition is to define mathematical methods based on which standards for asymmetric cryptotransformations, primarily electronic signatures, as well as asymmetric ciphers and key encapsulation protocols can be developed. Three electronic signature schemes – Crystals-Dilithium, Falcon and Rainbow become the finalists of the third stage of the NIST PQC competition according to the results of the second stage. The first two are based on the mathematics of algebraic lattices, and Rainbow is based on multivariate transformations. Currently, a comprehensive analysis of the finalists is an important task for the entire global crypto community. The vast majority of schemes that have become finalists or alternative algorithms are based on problems in the theory of algebraic lattices. Special attention was also paid to the Rainbow electronic signature scheme based on multivariate transformations. The purpose of this work consists in a preliminary analysis of existing attacks on promising electronic signature Rainbow, definition of requirements to the system-wide parameters to ensure cryptographic stability of at least 512 bits against classical and 256 bits against quantum cryptanalysis, as well as development and practical implementation of Rainbow algorithms for generating system-wide parameters for 512 bits against classical and 256 bits against quantum cryptanalysis.